Il ruolo dell’entropia come descrittore fenomenologico delle reazioni chimiche - Motta, Alessandro (Chimica nella Scuola, 2024)
The presentation of the second law of thermodynamics in high school and early university teachings often leaves students with a sense of elusive abstraction, condensed into the expression “entropy measures disorder”. This could be avoided by treating entropy more specifically as a property derived from the analysis of heat exchanges between the system and the surroundings. In this contest, starting from a modern reinterpretation of Carnot’s work on the efficiency of heat engines, it would be helpful to delve into the analytical derivation of entropy associated with an isothermal expansion process, demonstrating how such a process is intimately related to the thermodynamic explanation of chemical equilibrium. Furthermore, it would be beneficial to explore the historical motivations that led to the formulation of the third principle to clarify its chemical importance in deriving reaction entropy.